2011
DOI: 10.1111/j.1469-8137.2011.03684.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness analyses of Arabidopsis thaliana mutants depleted of FtsH metalloproteases and characterization of three FtsH6 deletion mutants exposed to high light stress, senescence and chilling

Abstract: Summary• Darwinian fitness analyses were performed, comparing single ftsh mutants with wild-type Arabidopsis thaliana plants grown under controlled laboratory conditions and in the field, by measuring plant size, survival rate, and silique and seed production.• Additionally, three genotypes of DFtsH6 were analysed, under controlled growth conditions, with respect to both their ability to degrade the light-harvesting complex of photosystem II during senescence and light acclimation.• In the field, substantial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…A similar role might exist for its close relative in A. thaliana, AtFtsH11. Wagner et al (2011) argue that AtFtsH11 is exclusively located in the chloroplast envelope but not mitochondrion, and importantly, that knockout of AtFtsH11 leads to a diminished level of several subunits of the protein transport machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar role might exist for its close relative in A. thaliana, AtFtsH11. Wagner et al (2011) argue that AtFtsH11 is exclusively located in the chloroplast envelope but not mitochondrion, and importantly, that knockout of AtFtsH11 leads to a diminished level of several subunits of the protein transport machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Instead AtFtsH6 was recently reported to be involved in regulating acquired thermotolerance, or "thermomemory", by degrading the plastidial heat shock protein HSP21 (Sedaghatmehr et al 2016). A previously suggested crucial role for AtFtsH6 in degrading LHCII, the light-harvesting complex of PSII (Zelisko et al 2005), now seems less likely (Wagner et al 2011).…”
Section: Multiplicity Of Ftsh In Photosynthetic Eukaryotesmentioning
confidence: 99%
“…It has been shown that a metalloprotease FtsH6 is involved in the cleavage of the Lhcb1 protein in high light acclimation and of the Lhcb3 subunit during dark-induced senescence in A. thaliana (Zelisko et al 2004(Zelisko et al , 2005. However, Wagner et al (2011) strongly argues that FtsH6 is not involved in LHCII degradation.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, four proteolytically inactive FtsHs (designated as FtsHi) are targeted to chloroplasts34. FtsH6 has high-sequence similarity to FtsH2 and FtsH8 (refs 32, 35). Involvement of FtsH6 in degradation of the PSII light harvesting proteins Lhcb1 and Lhcb3 during dark-induced senescence or high-light treatment has been demonstrated in vitro 36, however, additional studies have so far not revealed an in vivo function of FtsH6 in high light acclimation or any other biological process3235.…”
mentioning
confidence: 99%
“…FtsH6 has high-sequence similarity to FtsH2 and FtsH8 (refs 32, 35). Involvement of FtsH6 in degradation of the PSII light harvesting proteins Lhcb1 and Lhcb3 during dark-induced senescence or high-light treatment has been demonstrated in vitro 36, however, additional studies have so far not revealed an in vivo function of FtsH6 in high light acclimation or any other biological process3235. Notably, FtsH6 is expressed at very low levels in plants grown at normal growth temperature, but is highly induced after heat treatment in Arabidopsis (Arabidopsis eFP Browser; http://bar.utoronto.ca/efp_arabidopsis) and other species across the plant kingdom including the dicot crops rapeseed ( Brassica napus 37) and tomato ( Solanum lycopersicum 38), and the monocot crops wheat ( Triticum aestivum 39) and sorghum ( Sorghum bicolor 40).…”
mentioning
confidence: 99%